Associations between non-traditional lipid parameters and normoglycemic reversion in Chinese adults with prediabetes: a retrospective analysis - Huang, Cheng; Zhang, Yuhang; Yang, Xiaoqing; Li, Guofeng; Gao, Zhichao (Frontiers in Endocrinology, 2025)
BackgroundPrediabetes is a critical precursor to type 2 diabetes and poses an increasing global health challenge, particularly in China. While many individuals with prediabetes can revert to normoglycemia through lifestyle interventions, the impact of non-traditional lipid parameters on this process requires further investigation. Understanding the associations between these lipid parameters and glycemic recovery could inform more effective prevention strategies.MethodsThis study analyzed data from the Dryad public database, focusing on a cohort of 14,735 Chinese adults with prediabetes. Multivariate logistic regression models assessed the association between twelve lipid parameters and normoglycemia. Two-piecewise logistic regression was used to identify inflection points. Stratified and sensitivity analyses were conducted by age, sex, BMI, and family history of diabetes. The Area Under the Curve was calculated to compare predictive performance.ResultsDuring a mean follow-up of 2.94 years, 6,406 out of 14,735 participants with prediabetes (56.53%) reverted to normoglycemia. Multivariate logistic regression showed that lower levels of the atherogenic index of plasma (AIP), remnant cholesterol (RC), RC/HDL-C ratio, and LDL-C, as well as higher HDL-C, were significantly associated with a higher likelihood of normoglycemia. Except for HDL-C, all lipid parameters showed non-linear relationships with normoglycemia. While all lipid indices displayed modest discriminative ability (AUC > 0.5), AIP demonstrated the highest area under the curve (AUC = 0.579, 95% CI: 0.569–0.588). Subgroup and sensitivity analyses confirmed stronger associations in females, younger individuals (< 50 years), and those with lower BMI (< 24 kg/m²).ConclusionAIP, RC, and the RC/HDL-C ratio were strongly associated with reversion to normoglycemia among Chinese adults with prediabetes. AIP showed the strongest and most consistent relationship, especially in younger females with lower BMI.